Teachers’ Perspective On Standardized Test (Lembaga Penelitian dan Pengabdian Nasyarakat Universitas Pakuan, 2018)
Validity and reliability are the minimal characteristics of standardized test. Both of characteristics are fundamental requirement in measuring students’ achievement cognitively because the quality test will achieve quality achievement. The research conducted to describe teachers’ perspective on standardized test. As much as 20 respondents are chosen purposefully. Qualitative approach with descriptive method are used concerning this research. Observation, documentation and interview are the tools of gaining qualitative data. The findings show that 85% from the 20 respondents knew the terminology of standardized test (validity and reliability) but do not practice it. As much as 80% never validate the test by their self. As much as 20 % from 20 respondents do not understand how to validate the test manually or electronically. The conclusion of the research are the teachers have various perspective towards standardized test. Some teachers assume that the test should be standardized and some have other perceptions.